Managing stress and conflict in libraries - Pantry, Sheila ca. 20./21. Jh (Facet Pub., 2007)
Stress and conflict in the workplace undermine performance and can make people mentally and physically ill. Research indicates that ever-increasing numbers of people are experiencing excessive pressure of this kind in our rapidly changing world of work. This applies to libraries and information organizations as much as anywhere; indeed they can be particular targets for verbal and non-verbal violent behaviour because of their accessibility to the public. In addition, as in all organizations, a certain proportion of library staff is suffering aggression, abuse, bullying or harassment from a work colleague. Tackling - and preventing - these situations effectively is a responsibility for management under health and safety legislation in the UK and many other countries.